2006
DOI: 10.1080/00016480500266008
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against inner ear proteins in patients with delayed endolymphatic hydrops and unilateral juvenile deafness

Abstract: Among 8 patients with the contralateral type of DEH, 6 (75%) showed at least 1 reactive band on Western blotting. The protein that reacted most frequently had a molecular weight of 28 kDa, which was consistent with our previous results. Among 18 patients with unilateral juvenile deafness, 5 (28%) showed reactive bands, exclusively at 68 kDa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Damage to the inner ear can cause profound hearing loss by exposing the immune system to previously sequestered inner ear proteins, which may result in the production of antibodies against the inner ear, as the inner ear contains thousands of proteins. 22 Animal models used to investigate AIED have shown that there is no anatomic barrier to the systemic circulation within the cochleovestibular compartment. 11 The endolymphatic sac contains immunocompetent tissues capable of immune responses.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to the inner ear can cause profound hearing loss by exposing the immune system to previously sequestered inner ear proteins, which may result in the production of antibodies against the inner ear, as the inner ear contains thousands of proteins. 22 Animal models used to investigate AIED have shown that there is no anatomic barrier to the systemic circulation within the cochleovestibular compartment. 11 The endolymphatic sac contains immunocompetent tissues capable of immune responses.…”
Section: Pathophysiologymentioning
confidence: 99%
“…3 The inner ear antigens targeted by the immune system have not yet been identified, even though numerous reports of progressive hearing loss associated with systemic autoimmune diseases have been published. 22 Cogan's syndrome, Behcet's disease, relapsing polychondritis, systemic lupus erythematosus, rheumatoid arthritis, polyarteritis nodosa, and inflammatory bowel disease have all been linked with SNHL and dizziness. Audiovestibular disease control or management with immunosuppressive drugs has been effective in reversing or stabilizing hearing loss in some of these patients.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Suzuki reported contralateral DEH in an adolescent with unilateral deafness 10 . This contralateral occurrence of hydrops may have been due to autoimmune attack on the DEH ear 10 …”
Section: Introductionmentioning
confidence: 96%
“…9 Suzuki reported contralateral DEH in an adolescent with unilateral deafness. 10 This contralateral occurrence of hydrops may have been due to autoimmune attack on the DEH ear. 10 However, these studies are still inadequate to determine the underlying causes and genetic factors associated with DEH pathology.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation